THE INFLUENCE OF VARIETAL PROPERTIES ON THE FORMATION OF YIELD OF MAIZE HYBRIDS - Марініч, Любов; Єланська, Людмила (SWorldJournal, 2024)
Topicality. In market conditions, a necessary condition is the competitiveness of production due to the improvement of culture cultivation technology and optimal indicators of economic efficiency. Therefore, the issue of yield and value of corn grain of v